Efektivitas Komunikasi Interpersonal dalam Meningkatkan Wawasan Pembelajaran Mahasiswa Fakultas Ilmu Sosial di Masa Pandemi - Hasibuan, Apri Gunawan; Alfikri, Muhammad; Faishal, Muhammad (Medan Resource Center, 2023)
This research aims to determine the effectiveness of interpersonal communication in enhancing the learning insights of students from the Faculty of Social Sciences during the pandemic. It also seeks to understand the responses of students from the Faculty of Social Sciences, State Islamic University of North Sumatra, regarding the limited teaching and learning activities during the pandemic. The research aims to identify the obstacles faced during online learning and assess the effectiveness of interpersonal communication in the learning process. Additionally, it aims to determine the effectiveness of online learning compared to face-to-face or in-person learning methods. This research adopts a qualitative research method. The informants in this study consist of four students from the Faculty of Social Sciences. Data collection techniques involve conducting in-depth interviews and library studies. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this study aim to determine the effectiveness of interpersonal communication in enhancing learning in the Faculty of Social Sciences during the pandemic. It also aims to identify the efforts made to enhance the learning ethos during the pandemic.